Immunohistochemical study of the expression of fatty acid synthase and Ki-67 in salivary gland tumors - do Prado, Renata Falchete; da Silva Machado, Ana Lourdes [UNESP]; Dias Colombo, Carlos Eduardo; Carvalho, Yasmin Rodarte [UNESP] (Wiley-Blackwell, 2011)
BACKGROUND: The enzyme fatty acid synthase plays a fundamental role in the biosynthesis of fatty acids. Several recent studies have demonstrated a high fatty acid synthase expression in malignant tumors. Few studies have been conducted in oral and salivary gland tumors describing the fatty acid synthase expression.METHODS: This study evaluated and compared, by immunohistochemical reaction, the expression of fatty acid synthase and Ki-67 in salivary gland tumors. The immunohistochemical study used the streptavidin-biotin-peroxidase technique, with antibodies anti-fatty acid synthase and anti-Ki-67. The fatty acid synthase was analyzed by scores, considering the intensity of labeling, quantity of labeled cells and histological component. The Ki-67 was analyzed by counting of one thousand cells, calculating the quantity of positive cells in regions with higher density of labeling. Statistical analysis was performed using the Pearson and Mann-Whitney correlation tests.RESULTS: There was greater fatty acid synthase expression in pleomorphic adenoma compared to other tumors, and predominance of Ki-67 in malignant tumors. Among these, the mucoepidermoid carcinoma presented the highest proliferation rate. The expression of fatty acid synthase and Ki-67 did not present correlation between the tumors analyzed, except in pleomorphic adenomas, with statistically significant relationship between them.CONCLUSION: It is suggested that the fat metabolism in salivary gland tumors is related to maintenance of cell differentiation. Its expression prevailed in benign tumors, while Ki-67 prevailed in the mucoepidermoid carcinoma, demonstrating its high proliferation rate, followed by the cystic adenoid carcinoma and polymorphous low grade adenocarcinoma. J Oral Pathol Med (2011) 40: 467-475
Keywords: fatty acid synthase; immunohistochemistry; Ki-67; salivary gland tumors